2013
DOI: 10.1287/orsc.1120.0780
|View full text |Cite
|
Sign up to set email alerts
|

The Embeddedness of Networks: Institutions, Structural Holes, and Innovativeness in the Fuel Cell Industry

Abstract: P lentiful research suggests that embeddedness in alliance networks influences firms' innovativeness. This research, however, has mostly overlooked the fact that interorganizational ties are themselves embedded within larger institutional contexts that can shape the effects of networks on organizational outcomes. We address this gap in the literature by arguing that national institutions affect the extent to which specific network positions, such as brokerage, influence innovation. We explore this idea in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 159 publications
(110 citation statements)
references
References 91 publications
(100 reference statements)
4
103
0
3
Order By: Relevance
“…Despite the advantages of international knowledge brokerage, transferring new knowledge from developed countries to developing countries is associated with uncertainty because recontextualizing knowledge originating from developed countries requires complementary assets (Krueger, 2000;Shane & Venkataraman, 2000;Simon, Houghton, & Aquino, 2000). Thus, the effectiveness of international knowledge transfer is contingent on institutional factors that may hinder or facilitate the acquisition of complementary assets (Batjargal, Hitt, Tsui, Arregle, Webb, & Miller, 2013;Caligiuri, 2014;Vasudeva, Zaheer, & Hernandez, 2013). Research has shown that a cooperative relationship with the local government in developing countries assists knowledge brokers in acquiring complementary resources and external legitimacy (Luo, 2001;Spencer, 2003).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Despite the advantages of international knowledge brokerage, transferring new knowledge from developed countries to developing countries is associated with uncertainty because recontextualizing knowledge originating from developed countries requires complementary assets (Krueger, 2000;Shane & Venkataraman, 2000;Simon, Houghton, & Aquino, 2000). Thus, the effectiveness of international knowledge transfer is contingent on institutional factors that may hinder or facilitate the acquisition of complementary assets (Batjargal, Hitt, Tsui, Arregle, Webb, & Miller, 2013;Caligiuri, 2014;Vasudeva, Zaheer, & Hernandez, 2013). Research has shown that a cooperative relationship with the local government in developing countries assists knowledge brokers in acquiring complementary resources and external legitimacy (Luo, 2001;Spencer, 2003).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…While, for instance, Vasudeva, Zaheer and Hernandez (2013) show that the innovativeness of firms is enhanced by their location in a coordinated market context (see also Lehrer 2000 andLange 2009), Casper, Lehrer and Soskice (1999) and Casper (2009) suggest that the institutional environment of British firms might be more conducive to innovation than the German one. These contrasting findings may be due to the fact that the specific impact of national institutions on the management of innovation tensions has not been sufficiently accounted for.…”
Section: Tensions Of Creativity and Innovationmentioning
confidence: 99%
“…Scholars have suggested that inter-organisational networks are critical for innovation performance (Vasudeva et al, 2013;Schilling andPhelps, 2007, Reagans andMcEvily, 2003), showing that a great number of direct ties positively impacts innovation performance (Owen-Smith and Powell, 2004;Tsai, 2001). However, the costs of managing too many relationships can outweigh the benefits of knowledge creation, resulting in a negative effect on innovation (Hansen, 2002).…”
Section: Strategic Alliance 3211 Direct Relationmentioning
confidence: 99%